Sosialisasi Penanggulangan Kebakaran Untuk Peningkatan Pengetahuan Dan Kesadaran Siswa SDN Sukadana Ciomas Serang - Oktaviana, Fadilla; Fitriani, Dini; Julianti, Vina; Asmalia, Hikmah; Khoiriah, Silvi; Pratama, Muhamad Yasin; Permana, Fajar (Jurnal Pengabdian Kepada Masyarakat, 2025)
The Community Service Program (PkM) with the theme “Fire Prevention Awareness at SDN Sukadana, Ciomas District, Serang Regency” was held on August 2, 2025, with the aim of improving the understanding and skills of students and teachers in dealing with fire risks in the school environment. The focus of the activity was on fire prevention efforts by providing knowledge about the causes of fires, preventive measures, and appropriate school safety procedures. The implementation method consisted of three main stages, namely coordination with the school and preparation of materials, interactive delivery of fire prevention and safety materials, and evacuation simulations and simple fire extinguishing practices using Fire Extinguishers (APAR) and wet cloths. The results of the activity showed a significant increase in participants' understanding of fire hazards, skills in using fire extinguishers, and disaster preparedness through evacuation simulation exercises. Teachers and students were able to understand evacuation routes, remain calmer in emergency situations, and foster a culture of safety in the school environment. This program not only provided practical experience but also built collective awareness of the importance of school safety and disaster preparedness from an early age. Thus, this activity contributed to creating a school ecosystem that is more responsive to disasters and can be used as a model for implementing mitigation programs in other schools.